Evaluation of fennel seed meal in broiler chickens' diets: impacts on performance, carcass traits, digestive enzymes, intestinal microbiota, blood metabolites, and economic feasibility - M. E. Ghonime; F. Abdelazeem; R. A. M. Ali; M. M. Hamed; W. A. Hassan; L. A. Almutairi; M. A. Alqahtani; S. H. Almasoudi; M. Alagawany (Archives Animal Breeding)
The present study evaluated the effects of fennel seed meal (FSM) on performance, carcass characteristics, lengths of digestive tract parts (cm), intestinal enzyme activity, intestinal microbiology, blood parameters, and economic efficiency in broiler chickens. One hundred 44 unsexed, 1 d old broiler chicks (Ross) were divided into four groups, each with 36 chicks, at random and into four replicates, each with 9 chicks. The first group was fed the basal diet (control group), while the second, third, and fourth groups (T1–3) were fed a diet with 5 %, 10 %, and 20 % fennel seed meal, respectively. Dietary treatments significantly affected all performance parameters at 5 weeks of age. Total protein, albumin, globulin, aspartate aminotransferase (AST), total cholesterol, and triglycerides significantly affected the results, while the alanine aminotransferase (ALT) and albumin–globulin ratios did not change substantially. The results revealed no significant difference in the activity of amylase, trypsin, and lipase (U dL−1) between the treatments. The chymotrypsin enzyme experienced a notable impact. There was a significant increase in the total digestive tract, small intestine, and cecum length (cm) in birds fed FSM compared to the control group. Moreover, including FSM in broiler diets increased lactic acid bacteria and reduced coliforms and clostridia. Net return and economic efficiency were increased with increasing FSM levels in broiler diets. It is concluded that FSM can be used in up to 20 % of broiler chicken diets to reduce feed costs without adverse effects on broilers' growth performance and public health.